Causes and Outcomes of Patients Presenting with Diplopia: A Hospital-based Study - Kumar, Nitin (Neuroophthalmology, 2021)
Diplopia or double vision has various aetiologies and often presents to the ophthalmologist. The purpose of our study was to study in detail the aetiology, progression, and outcome in patients of diplopia presenting to the ophthalmology department of a tertiary care centre. In a prospective observational study, all patients presenting to the emergency services and the outpatient department of a tertiary care centre over a period of 1 year were recruited. One hundred and sixty patients who presented with diplopia with a mean age of 40 (range 7–76) years were included. There were 112 (70%) males and 48 (30%) females. The most common cause for binocular diplopia was vasculopathy in 43 (28.66%) followed by trauma in 37 (24.66%). In those less than 20 years decompensating heterophorias were most common and had the best prognosis. Traumatic causes were common in the age group 20–40 years and vascular in the >40 years age group. For all other aetiologies, elderly patients had more resolution than young patients (p = .04). Larger deviation at presentation, younger age group, and a history of trauma were associated with late recovery (p = .03. p = .04 and p = .04, respectively).